Ley De Transparencia: Rol y Responsabilidad Social Del Revisor Fiscal En Colombia (2022)
Economic crimes such as fraud and corruption are reasons for scandals and concern on the part of Colombian society, private companies and government institutions, because they impede the growth and development of any nation. In Colombia, all economic sectors have presented ethical and integrity problems that generate patrimonial detriment, threaten the principle of going concern, bankrupt companies and generate unemployment. The Superintendency of Companies (2019) by external circular No No 115-000011 of 2008, indicates that Tax Audits are an exclusive function of public accountants in Colombia that play a very important role in the life of the country to the point that society places trust in this professional to make decisions regarding investment, savings, credit and certify their Financial Statements. The State, through the Superintendency of Companies, has given the Statutory Auditor the responsibility to detect and report crimes such as corruption, transnational bribery, money laundering, and the financing of terrorism in the exercise of his position, assuming responsibility to act in the public interest, in accordance with the provisions of law 2195 of 2022 (law of transparency, prevention and fight against corruption), law 1474 of 2011 (Anti-Corruption Statute), law 1778 of 2016, which included the obligation to report to criminal authorities a catalog of crimes that must be reported and exercise internal control in accordance with circular 100-0005 of december 24, 2020.